Impact of poor disease surveillance system on COVID-19 response in africa: Time to rethink and rebuilt - Abdullahi Tunde Aborode; Mohammad Mehedi Hasan; Shubhika Jain; Melody Okereke; Oluwakorede Joshua Adedeji; Ayah Karra-Aly; Ayoola S. Fasawe (Elsevier, 2021)
Infectious disease outbreaks have long posed a public health threat, especially in Africa, where the incidence of infectious outbreaks has risen exponentially. Although, Africa has witnessed several outbreaks of emerging and re-emerging infectious diseases such as Ebola virus disease and other epidemic-prone diseases, little attention has been given towards strengthening the health surveillance systems. However, the recent COVID-19 pandemic has uncovered the region's already due to inefficient and ineffective health surveillance systems. However, the impact posed by the COVID-19 pandemic on health systems in the region has been catastrophic, it has also stressed the importance of rethinking and focusing on lessons learned during the COVID-19 pandemic. In this paper, we examine how Africa's poor disease surveillance systems affected the responses and strategies aimed at COVID-19 containment. To ensure early disease outbreak identification and prompt public health interventions in Africa, the current disease surveillance and response mechanisms must be strengthened.